Additive manufacturing process for production of complex and oscillating POSS-based 4D structures - Nicole Gorohovsky; Ronen Verker; Noa Lachman (Virtual and Physical Prototyping)
A tailored printing index is employed to identify optimal parameters that yield uniform layer deposition and controlled actuator geometries. The resulting actuators exhibit robust shape memory responses, reliable gripping mechanisms, and oscillatory transformations upon thermal stimulation. Unlike conventional casting, this AM technique facilitates precise, selective material deposition, advancing the complexity of actuator designs without additional post-processing. These findings underscore the potential of AM to broaden the structural and functional versatility of bilayer actuator systems for advanced applications.